Expert SharePoint 2010 Practices - LLC, Winsmarts; Malik, Sahil; Farnhill, Brian; bin Rais, Razi.; Richard, Ed.; Musters, Ed.; Bishop, Darrin; McDermott, Matthew; Orange, Mark.; Loriot, Cory R.; Eddinger, Matt.; Ortiz, Doug.; et al. (Berkeley, CA : Apress : Imprint: Apress, 2011)
Expert SharePoint 2010 Practices is a valuable compendium of best practices, tips, and secrets straight from the most knowledgeable SharePoint gurus in the industry. Learn from the experts as you dive into topics like multitenancy, solution deployment, business intelligence, and administration. Our team of carefully chosen contributors, most with Microsoft's Most Valuable Professional (MVP) designation bestowed upon them, shares with you the secrets and practices that have brought them success in a wide variety of SharePoint scenarios. Each contributor is passionate about the power of SharePoint and wants to help you leverage the capabilities of the platform in your business—but in the proper way. Go beyond procedures and manuals, and benefit from hundreds of years of combined experience, which the authors of Expert SharePoint 2010 Practices provide in these pages. Learn from the masters and take control of SharePoint 2010 like you never have before with Expert SharePoint 2010 Practices!
Keywords: Microsoft software; Microsoft .NET Framework; Computers; Microsoft and .NET.; Information Systems and Communication Service